2019
DOI: 10.1002/anie.201903245
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Peaks in Simple Two‐Dimensional NMR Experiments from Chemical Exchange of Transverse Magnetisation

Abstract: Two‐dimensional correlation measurements such as COSY, NOESY, HMQC, and HSQC experiments are central to small‐molecule and biomolecular NMR spectroscopy, and commonly form the basis of more complex experiments designed to study chemical exchange occurring during additional mixing periods. However, exchange occurring during chemical shift evolution periods can also influence the appearance of such spectra. While this is often exploited through one‐dimensional lineshape analysis (“dynamic NMR”), the analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Chemical exchange in multi-dimensional (and often heteronuclear) experiments brings some new considerations [30][31][32]. Firstly, the impact of exchange broadening on resonance intensities is more severe.…”
Section: Multi-dimensional Nmr Experimentsmentioning
confidence: 99%
“…Chemical exchange in multi-dimensional (and often heteronuclear) experiments brings some new considerations [30][31][32]. Firstly, the impact of exchange broadening on resonance intensities is more severe.…”
Section: Multi-dimensional Nmr Experimentsmentioning
confidence: 99%
“…Several pulse sequences are available for analysis within TITAN, of which HSQC and HMQC are the most common experiments. It is important that the pulse sequence is correctly specified as this will strongly affect the results, as chemical exchange can have different effects on line-shapes in the indirect dimension of HSQC and HMQC experiments [ 40 ], as well as during coherence transfer periods [ 41 ].…”
Section: Data Acquisitionmentioning
confidence: 99%
“…However, not only is this approach limited by the need to avoid overlapping resonances—a particularly common problem in crowded spectra of IDPs—but additional uncertainty is introduced by the need to normalize the area under each cross peak, which may by highly broadened by chemical exchange. Lastly, because the pseudo-two-dimensional approach does not accurately consider the evolution of magnetization through the full pulse sequence, we have also shown that this approach can introduce systematic errors by neglecting differential relaxation in the slow-intermediate exchange regime [ 40 ] and phase distortions and cross peaks arising from chemical exchange during mixing and chemical shift evolution periods [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…These processes lead to line broadening effects in 1D spectra or change the appearance of cross peaks in 2D spectra. 18 2D NMR has been used extensively to extract quantitative information, especially due to the limited resolution in 1D spectra at low magnetic fields. 19,20 Slow exchange processes become observable by following the fate of longitudinal magnetization.…”
mentioning
confidence: 99%
“…Phototriggered reactions can be performed in situ with optical fibers inserted into the sample tube. , In addition to determining structure and concentrations, NMR is also a vital tool to study conformational changes or chemical exchange processes. These processes lead to line broadening effects in 1D spectra or change the appearance of cross peaks in 2D spectra . 2D NMR has been used extensively to extract quantitative information, especially due to the limited resolution in 1D spectra at low magnetic fields. , Slow exchange processes become observable by following the fate of longitudinal magnetization.…”
mentioning
confidence: 99%